Crude Oil Pipeline Security: Minimizing Illegal Tapping using â€œSOLIDSâ€ System - Muhammad Rais (Scientific Contributions Oil and Gas, 2020)
One of subsidiaries of Pertamina is Pertamina GasÂ which manage special task in operating crude oilÂ transportation ï‚±15,000 barrel oil per day (BOPD).Â In the operation still occur illegal tapping activitiesÂ and risk of pipeline product theft is a majorÂ concern to industry. In 2012, oil thieves drills 748Â illegal taps or an average 2 times every day. LossesÂ from transportation approximately 40% per dayÂ and loss revenue more than $20 million a year. TheÂ activities of illegal tapping by cutting intoÂ pipelines can cause pipeline ruptures andÂ explosions, leading to human casualties,Â destruction of property, and damage to theÂ environment.Â Pertamina Gas reported that illegal taps rise toÂ 400% from 2010 until 2013 and effort was taken toÂ minimize illegal tapping frequency and developsÂ integrated system that includes supervision andÂ security of assets along the pipeline calledÂ â€œSecurity and Oil Losses Management withÂ Integrated Detection System (SOLIDS)â€. ThisÂ system includes liquid management system (LMS),Â pipeline leak detection system (PLDS), securityÂ team patrol, emergency response team (ERT),Â radio communication-CCTV and corporate socialÂ responsibility (CSR).Â The implementation of SOLIDS is an effective oilÂ loss detection technologies and pipeline securityÂ that detect product thefts quickly and accuratelyÂ locate illegal tapping points. SOLIDS investmentÂ costs are still smaller than the company's lossesÂ due oil losses and environmental impact.Pertamina Gas has been succeeded in reducingÂ losses from illegal taps. In 2012 the number ofÂ illegal tapping cases 748 points and decreasedÂ significantly in 2018 as many as zero case.Â Consistent implementation of this system willÂ provide solution in reducing losses and illegalÂ tapping under all operational conditions.